Awareness of age-related changes in Norwegian individuals 50+. Short form questionnaire validation - Testad, Ingelin; Ushakova, Anastasia; Aakre, Jon Arild; Sabatini, Serena; Gjestsen, Martha Therese (Frontiers in Psychiatry, 2022)
Background: A questionnaire assessing awareness of positive and negative age-related changes (AARC gains and losses) was developed in the US and Germany, and validated for UK and Brazilian populations. In this study, we validated the short form measure (AARC-10 SF) in the Norwegian population aged 50 and over. In addition, the relationship between cognitive variables and AARC was examined. Methods: Cross sectional analyses of data from 1510 participants in the ongoing online PROTECT Norge study were used to explore and confirm the two-factor structure of AARC gains and AARC losses; reliability; measurement invariance across different population groups defined by sex, education level, employment, and in middle age, early old age, and advanced old age. We explored the relationship between AARC and demographic variables (defined in the same way as the population groups). Results: We confirmed the two-factor structure (gains and losses) of the Norwegian translation of the AARC-10 SF. We did not find mutual correlations between related items in gains- and losses, except for the physical health item from the gains dimension, which was positively correlated with all items of the losses dimension. Age, sex, marital status, employment, and university education predicted AARC gains and losses. Conclusions: The Norwegian translation of the AARC-10 SF captures individuals’ positive and negative self-perceptions age-related changes in their mental, physical, and cognitive health.